PENGARUH MODEL PEMBELAJARAN LEARNING START WITH A QUESTION (LSQ) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA TEMA PERISTIWA DALAM KEHIDUPAN DI KELAS V SDN 101777 SAENTIS - Shania Mayari; Nurhairani Nurhairani (JS (JURNAL SEKOLAH), 2020)
Abstract: The Influence Of Learning Start With A Question (LSQ) Learning Model On Critical Thinking Ability Students In Events In Life In Class V SDN 101777 Saentis. This type of research is a Pre-Experimental Design research with one group pretest-posttest design. The sample in this study were 29 students. Data collection in this study was carried out using essay and observation tests. The results showed that the learning model had an influence on students' critical thinking skills. Based on the results of normality tests the results of pretest Lo ˂ Ltable where 0.158 ˂ 0.163 with normal information, while the results of posttest Lo ˂ Ltable where 0.136 ˂ 0.163 with normal information. Then test the normality of the results of the pretest and posttest with normal information. The results of hypothesis testing using t-test at a significant level of 0.05 obtained tcount ˃ ttable where the tcount = 29.14 and the value of ttable at a significant level of 5% is 1.70. From the results of the hypothesis test analysis it can be concluded that there is a positive and significant influence between the Learning Start With A Question (LSQ) learning model on students' critical thinking skills on the themes of events in life in Class V SDN 101777 Saentis. Keywords: Learning Start Learning Model With A Question (LSQ), critical thinking skills. Abstrak: Pengaruh Model Pembelajaran Learning Start With A Question (LSQ) Terhadap Kemampuan Berpikir Kritis Siswa Pada Tema Peristiwa Dalam Kehidupan Di Kelas V SDN 101777 Saentis. Jenis penelitian ini adalah penelitian Pra-Eksperimental Design dengan jenis one group pretest-posttest design. Sampel dalam penelitian ini adalah 29 siswa. Pengumpulan data dalam penelitian ini dilakukan dengan menggunakan tes essai dan observasi. Teknik analis data menggunakan uji normalitas dan uji hipotesis. Berdasarkan hasil uji normalitas hasil pretest Lo ˂ Ltabel dimana 0,158 ˂ 0,163 dengan keterangan normal, sedangkan pada hasil posttest Lo ˂ Ltabel dimana 0,136 ˂ 0,163 dengan keterangan normal. Maka uji normalitas dari hasil pretest dan posttest dengan keterangan normal. Hasil uji hipotesis dengan menggunakan uji-t pada taraf signifikan 0,05 didapatkan thitung ˃ ttabel  dimana besar thitung = 29,14 dan nilai ttabel pada taraf signifikan 5% adalah 1,70. Dari hasil analisis uji hipotesis dapat disimpulkan bahwa terdapat pengaruh positif dan signifikan antara model pembelajaran Learning Start With A Question (LSQ) terhadap kemampuan berpikir kritis siswa pada tema peristiwa dalam kehidupan di Kelas V SDN 101777 Saentis.Kata Kunci: Model pembelajaran Learning Start With A Question (LSQ), kemampuan berpikir kritis.